Resilience in Carers of People With Young-Onset Alzheimer Disease. (March 2019) - Kimura, Nathália R. S.; Neto, José Pedro Simões; Santos, Raquel Luiza; Baptista, Maria Alice Tourinho; Portugal, Glória; Johannessen, Aud; Barca, Maria Lage; Engedal, Knut; Laks, Jerson; Rodrigues, Valeska Marinho; Dourado, Marcia C. N.
Young-onset Alzheimer disease (YOAD) causes psychological and emotional difficulties for carers. However, even in the face of considerable caregiving demands and burden, some carers are resistant to stress, which may be a sign of resilience. This study investigated whether the clinical symptoms of the person with YOAD might be associated with resilience in their carers. A consecutive series of 43 persons with YOAD and their 43 family caregivers were assessed. The carers showed moderate to high level of resilience, low level of anxiety and depressive symptoms, and moderate level of burden. No relationship was found between resilience and sociodemographic characteristics of both carers and care recipient and with clinical characteristics of persons with YOAD. A linear regression analysis showed that resilience was inversely associated with carers' depressive symptoms. The findings suggest that resilience may mainly be related to carers' mental health.